The role of electronic versus written order sets in inappropriate laboratory testing among hospitalized medical patients. (September 2021) - Brown, Ian; Tran, Allen; Soong, Christine; Okrainec, Karen
Highlights: Daily electronic lab orders was associated with higher rates of inappropriate indications. Daily electronic lab orders was associated with lower rates of discontinuation. Electronic order sets need appropriate indications and discontinuation interventions included. Abstract: Importance: Reducing inappropriate blood tests has been highlighted by Choosing Wisely as a key area of focus. Computer physician order entry is one modifiable contributor, but little is known about how computer ordering compares to paper methods when it comes to low-value laboratory testing. Objective: To determine which method of order entry is associated with a greater amount of appropriate lab testing. Furthermore, to identify ordering patterns for more targeted interventions in future. Design: We conducted a retrospective observational cohort study of inpatients discharged at two hospitals (one site uses paper order sets, while the other uses electronic order sets). Setting: General internal medicine wards at two Canadian teaching hospitals. Participants: At site 1 (electronic orders), all general internal medicine discharges from May 2015 and February 2016. At site 2 (paper orders), all general internal medicine discharges from April 15, 2015 to May 26, 2015. Main Outcome(s) and Measure(s): Main outcome was the percentage of inpatient discharges at each site with orders for daily laboratory tests for three days on admission. Secondary measures include proportion of tests with appropriate indications and rates of discontinuation of daily laboratory tests. Results: We reviewed 395 discharges with a mean patient age of 69.5 ± 18.9 years and mean length of stay of 12.1 days. Daily laboratory tests were more common with paper orders (site 2) compared to electronic order sets (site 1) for complete blood count (CBC) (90.8% vs. 68.5%, p < 0.001), electrolytes (93.8% vs 71.5%, p < 0.001), and creatinine (93.8% vs 70.0%, p < 0.001) testing. However, paper orders for daily laboratory tests were more often appropriate, both in CBC (76.3% vs. 38.9%, p < 0.001) and electrolyte/creatinine (80.3% vs 44.2%, p < 0.001) testing. Discontinuation of daily labs occurred more often with paper orders (35.4% vs. 6.7%, p < 0.001). Conclusions and Relevance: Compared to written orders, daily laboratory testing using electronic ordering was associated with higher rates of inappropriate indications and lower rates of discontinuation. Our results support interventions aimed at ensuring electronic order sets incorporate appropriate indications and a mechanism for discontinuation of daily lab orders. Further studies aimed at understanding how the process of completing paper or electronic orders influence appropriateness of daily laboratory orders are needed to further minimize inappropriate testing.